Genetic diversity of Lotus corniculatus in relation to habitat type, species composition and species diversity - Eleni M. Abraham (2018)
© 2015 Elsevier Ltd. The genetic variability of Lotus corniculatus, a common and important fodder legume, was studied in relation to habitat type and to species diversity at a local level. The study was conducted in Cholomontas mountain, northern Greece, at altitudes of 760-870 m. Genetic material was selected from four forested, at the edge of forest, and four open grassland sites, and was studied with the aid of ISSR molecular markers. The plant cover at each study site was measured and the floristic composition was estimated. The percentage of graminoides increased in grassland sites with high grazing intensity, while the abundance of legumes, including L. corniculatus, forbs and woody species, increased in forested sites with low grazing intensity. Gene diversity HEwithin the studied populations of L. corniculatus ranged from 0.167 to 0.213 and Shannon index (I) from 0.269 to 0.340. Genetic differentiation was detected between habitats as well as among the populations in each habitat, although it was low, 3% and 7% respectively. However, genetic differentiation was significant within the populations (90%). Genetic diversity of L. corniculatus was not correlated with species diversity (richness and evenness) either within or between populations, while was negatively correlated with L. corniculatus abundance.